Development of universal model of kinetics of bioremediation stationary process with substrate inhibition - Bakharevа Anna; Shestopalov Oleksіi; Filenko, Olesya; Kobilyansky, Boris (Eastern-European Journal of Enterprise Technologies, 2016)
The results of stationary laboratory experiments are analyzed on the basis of the specific (per unit biomass) degradation rate of environmental pollutants. The presence of substrate inhibition for both gaseous, and water-dissolved pollutants is revealed. The phenomenological approach, which takes into account two obvious phenomena in a simple form: the contact of a microorganism with the substrate molecule and the inhibitory effect of the environment on it is applied to the analytical description of the relationship between the bio-oxidation rate and the pollution concentration. Numerical values of empirical coefficients of relationships for the investigated processes are calculated. The differential equation, describing the kinetics of biochemical degradation at the macro-level is proposed. The macrokinetic mathematical model of bioremediation is defined as a system of two functions, quantitatively reflecting the pollutant specific oxidation rate-concentration relationship and the concentration-time relationship, and satisfying the relationship of these parameters in a differential form. The concentration-time relationship is determined in the form of both the numerical integration algorithm and the approximate formula. The relevance and versatility of the proposed model for the investigated processes are proved. The resulting model is the basis for the quantitative description of non-stationary processes in bioreactors.